Scalar vicissitudes and minute creatures: reexamining insects as cinematic subjects in Microcosmos and Life in the Undergrowth - Mikkola, Heidi (Routledge, 2026)
This article examines insects as subjects in the documentary moving image and scalar vicissitudes in two different kinds of wildlife documentaries: Life in the Undergrowth (2005) and Microcosmos (1996). Western relationships with insects are intimately tied to technology and visual perception. The mass extinction of insects remains largely overlooked; however, their disappearance poses a significant threat to ecosystems and biodiversity. I argue that insect documentaries have roots in early depictions of microscopic illustrations as well as in the tradition of wildlife documentary. Although the wildlife documentary genre focuses on animals, its narrative tradition lies in representing bigger animals, usually mammals. By contrast, the theorization of cinematic scales lies in relation to the human figure. The convergence of these visual traditions raises considerations regarding documentaries about insects, while it also prompts us to reflect on the ethics of scale in the human – insect relationship. I argue that examining insects as proper cinematic subjects contests anthropocentrism in cinematic scales and rethinks understandings of ecological relations. The article examines the spatial scales and framings of the films, especially close-ups, when the subject of the framing is an insect instead of a human figure. I argue that taking the insect instead of the human body as the reference point shifts the scalar framework through which these films operate, unsettling the human body’s role as the implicit measure of scale. This shift brings questions of image size and scale to the fore and makes visible alternative ecological relations.
Keywords: Insects; scale; wildlife documentary; close-up; anthropocentrism; fi=Viestintätieteet|en=Communication Studies|